The identity of Nyssa yunnanensis (Cornaceae) - Tan, Yun-Hong; Deng, Yun Fei (Phytotaxa, 2016)
Nyssa yunnanensis was previously recognized as an endemic and critically endangered Chinese species. It is similar to N. javanica, but differs in bearing thicker leathery leaves, branchlets, pedicels, and leaves abaxially persistently pilose. Examination of the herbarium specimens reveals that N. yunnanensis is well identical with N. bifida, which was previously reduced to the synonymy of N. javanica. Nyssa bifida is herein re-instated since it has priority over N. yunnanensis. The name N. bifida is lectotypified.